CUL4A as a marker and potential therapeutic target in multiple myeloma - Yougang Yang; Shanan Wang; Jinghong Li; Shipeng Qi; Debing Zhang (Tumor Biology)
Multiple myeloma is the most common cause of death of hematological malignancy worldwide. Cullin 4A has been proposed as oncogene in several types of human cancer, but the expression and function of cullin 4A in multiple myeloma remain unclear. Here, we demonstrate that cullin 4A plays an oncogenic role in multiple myeloma development. The expression of cullin 4A was detected by quantitative real-time polymerase chain reaction in multiple myeloma patients and multiple myeloma cell lines. In addition, silencing of cullin 4A with small interfering RNA was performed in human multiple myeloma cells, and the impact on proliferation, cell cycle, apoptosis, migration, and invasion of the multiple myeloma cells was analyzed. We found that the level of cullin 4A in serum samples was significantly upregulated in patients with multiple myeloma compared with healthy control subjects. Knockdown of cullin 4A via small interfering RNA inhibited the proliferation of the multiple myeloma cell lines by delaying cell-cycle progression and increasing apoptosis. cullin 4A downregulation inhibited multiple myeloma cell migration and invasion in vitro. Our results suggested that cullin 4A could be a promising therapy target in multiple myeloma patients.